(untitled) (Scientific journal of the Fergana State University, 2025)
Fiction describes and expresses through words. We cannot imagine works of art without means of artistic imagery, because with their help we can vividly describe what is being described in the work, vividly express feelings and experiences. Reading the novel “The Scorpion From the Altar ”, we understand how appropriate the means of artistic imagery are used, and we witness the efforts made by the translator to restore these means in the process of translating into English. In this article, we will study the importance of means of artistic imagery in the translation of the novel “The Scorpion From the Altar” into English and how they contribute to the overall effect of the text.